A Case of Attempted Suicide by Cerbera odollam Seed Ingestion - Michelle Bernshteyn; Steven H. Adams; Kunal Gada (Case Reports in Critical Care)
We report a case of attempted suicide by Cerbera odollam seed ingestion by a transgender patient who was successfully treated at our hospital. While the C. odollam plant has multiple practical and ornamental functions, its seeds have traditionally been utilized for suicidal and homicidal purposes in many parts of the world. Physicians should be aware of the presentation, diagnosis, and treatment of C. odollam ingestion given the current ease of availability of these seeds in the United States and the increased reports of suicide attempts.